2007
DOI: 10.1086/514333
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Boxy Bulge and Bar of the Andromeda Spiral Galaxy

Abstract: A new, 2.8 deg^2 J,H,K_s infrared survey from the 2MASS 6x program across the extent of the optical disk of the Andromeda (M31) galaxy provides a clear view of the M31 center almost completely unfettered by dust extinction, and reveals a high contrast bulge with extremely boxy isophotes dominating the NIR light to a semi-major axis of ~700''(2.6 kpc). The inner bulge (<~50'') is relatively circular, but shows some isophotal twisting. Beyond this, the ellipticity and boxiness of the bulge increase with radius -… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
120
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(131 citation statements)
references
References 32 publications
10
120
0
1
Order By: Relevance
“…This is because after the pioneer work of Lindblad (1956) several other papers have pointed out in the inner region of M 31 the presence of morphological structures, such as a bar and a bulge, associated with streaming motion and non-circular orbits (e.g. Stark & Binney 1994;Athanassoula & Beaton 2006;Gordon et al 2006;Beaton et al 2007). In particular Berman (2001); Berman & Loinard (2002) have shown that the anomalous velocities observed in the inner region of M 31 can be explained as the response of the gas to the potential of a triaxial rotating bulge.…”
Section: Why Exclude the Innermost Region From Fittingmentioning
confidence: 99%
“…This is because after the pioneer work of Lindblad (1956) several other papers have pointed out in the inner region of M 31 the presence of morphological structures, such as a bar and a bulge, associated with streaming motion and non-circular orbits (e.g. Stark & Binney 1994;Athanassoula & Beaton 2006;Gordon et al 2006;Beaton et al 2007). In particular Berman (2001); Berman & Loinard (2002) have shown that the anomalous velocities observed in the inner region of M 31 can be explained as the response of the gas to the potential of a triaxial rotating bulge.…”
Section: Why Exclude the Innermost Region From Fittingmentioning
confidence: 99%
“…Bars are frequent in spiral galaxies (60 to 75% are barred according to the bar strength; e.g., Verley et al 2007), and it is likely that M 31 is barred or has been barred, because of its triaxial boxy bulge (Beaton et al 2007). However, up to now, the bar is not visible in the gas in either the morphological or kinematical data.…”
Section: Scenario 2: a Possible Barmentioning
confidence: 99%
“…the angle between the bar and the major axis of the galaxy is between 20 and 30 • . The size of the boxy-bulge is 1.4 kpc in radius, and the total length of the bar would be 4 kpc in radius, because a thin bar is identified beyond the boxy bulge (Beaton et al 2007). …”
Section: Previous Bar Propositions In M 31mentioning
confidence: 99%
“…M 31 is no exception; although Hubble classified it as normal type Sb, it is likely to possess a stellar bar. The presence of a bar in M 31 is suggested by its boxy bulge, which is conspicuous in infrared imaging 5,20 and is aligned almost parallel to the galaxys major axis. The boxy bulge might be an inflated bar, or it may hide a thinner parallel bar (at about 10 degrees from the major axis).…”
mentioning
confidence: 95%